PENGARUH SISTEM PENGENDALIAN INTERN, KEPATUHAN, DAN PEMBERIAN TAMBAHAN PENGHASILAN BERSYARAT (TPB) TERHADAP PERILAKU ETIS PEGAWAI (Studi Kasus Pada Badan Pengelolaan Pendapatan Daerah Pemerintah Kabupaten Jayapura) - Abriyanti, Andhika Dwi; Rofingatun, Siti; Sanggenafa, Mariolin A. (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2020)
This study aims to determine the effect of internal control, compliance, additional income conditionalÂ on the ethical behavior of employees of the revenue management agency in Jayapura district. ThisÂ research is correlation research or relationship, with the unit of analysis being studied are employeesÂ who work in the BAPENDA office with a total sample of 40 employees. The questionnaire was testedÂ for validity and reliability before testing the research data, the test equipment used in this study usedÂ the classical assumption test which included the normality test for linearity heteroscedasticity and theÂ linearity test data analysis method used was multiple linear regression analysis using the statisticalÂ analysis tool SPSS 25.The results ofthis study indicate that the Internal Control System variable doesÂ not have a significant effect on employee ethical behavior, while the Compliance and Supplementary Conditional variables have a significant effect on employee ethical behavior. Variables InternalÂ control, compliance and management compensation together (simultaneous) have a positive andÂ significant effect on employee ethical behavior.